Ortega y Camus: los aguijones socráticos en el espacio público - Jahanbegloo, Ramin (Revista de Estudios Orteguianos, 2021)
Camus’ praise of Ortega y Gasset reflects similarities in their understanding of the role of the intellectual in society. This includes political discourse and the resistance to totalitarianism and the mind set that it involves. Drawing fundamentally on The Revolt of the Masses and Morbid Democracy, the autor underlines the life enhancing role of philosophy.